Analisis Kognitif Siswa Kelas VI dalam Menyelesaikan Soal Cerita Geometri Lingkaran - Astrit Santika; Della Alfina; Rio Norendra (CV. ITTC INDONESIA, 2026)
This study aims to analyze students' cognitive abilities in solving word problems on the topic of circular geometry. The study used a quantitative descriptive approach with an exploratory design on six sixth-grade students at a public elementary school in Palangka Raya City, selected through purposive sampling. The instrument consisted of five essay questions based on the revised Bloom's Taxonomy (C2–C4). The results showed that the average cognitive ability of students was in the high category (80%), with three students categorized as very high, one student categorized as high, and two students categorized as low. At the understanding level (C2), students were generally able to recognize the elements of a circle, but their understanding was still superficial. At the application level (C3), low-ability students experienced difficulty modeling the problem and performing calculations. At the analysis level (C4), only high-ability students were able to provide logistical reasoning. This study contributes to the compression of students' thinking processes in solving word problems on circular geometry as a basis for developing HOTS-based learning strategies and scaffolding.